Yield and economic evaluation of wild almond seeds in Karebass site, Cheharmahal & Bakhtiari, Iran - Razieh Sharifpour-Latooni; Ali Jafari; Hasan Jahanbazi Goujani; Yousef Askari (تحقیقات جنگل و صنوبر ایران, 2015)
Wild almond (Amygdalus arabica Olivier) is one of the main forest trees with high non-wood values in Zagros Mountains of Iran. The study carried out in Karebass area, Cheharmahal & Bakhtiari province and measured seed production capacity in wild almond across eight crown diameter classes (0.5 to 4 m) at individual level. Five trees were chosen in each crown diameter class randomly at different geographical aspects (mainly north and southwards). All major tree dimensions including cross crown diameters, height, sprouts numbers, diameter of thickest sprout at soil lever as well as the total amount of produced seeds were measured in situ and/or ex situ. The values were checked for normal distribution, and analysis of variance of growth characteristics, seed size and total yield were carried out across different crown classes and geographical aspects. Moreover, the significance of differences was assessed separately using a Duncan multiple range test. The results showed that the diameter of thickest sprouts, shrub height, and total seed yield were highly regulated (99% confidence interval) by crown diameter classes. Potential yearly seed yield in the study site was assessed to be 12.4 tons. The fruit and seed yields have been speculated as the main source of income for local inhabitants.